2009
DOI: 10.1577/m08-175.1
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Fishery Quality Index for Portuguese Streams

Abstract: Abstract.-There is a need to quantify the multivariate quality of a recreational fishery at the site scale to better communicate the relative quality among sites to the public and anglers. Borrowing on the general approach of multimetric indices of biotic integrity (IBIs), we developed fishery quality indices (FQIs) from species quality indices (SQIs) based on measures of fish abundance and size structure for northern and central Portuguese streams. Our FQIs showed regional patterns indicating a range in fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…This result is concordant with the findings of Oliveira et al [44] in the least disturbed and forested areas of northern and central Portugal, who found more and larger individuals in midelevation streams with gentler slopes. Possibly, lower gradient sites, with intermediate flow levels, tend to show higher diversity of available habitats for fish.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is concordant with the findings of Oliveira et al [44] in the least disturbed and forested areas of northern and central Portugal, who found more and larger individuals in midelevation streams with gentler slopes. Possibly, lower gradient sites, with intermediate flow levels, tend to show higher diversity of available habitats for fish.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the density-based metrics strongly influenced by the regional gradient R1 displayed unimodal relationships, indicating lower fish densities in the northern reaches that had higher catchment relief and slope, and strong runoff events, and higher densities at some intermediate levels. This result is concordant with the findings of Oliveira et al [44] in the least disturbed and forested areas of northern and central Portugal, who found more and larger individuals in midelevation streams with gentler slopes. Possibly, lower gradient sites, with intermediate flow levels, tend to show higher diversity of available habitats for fish.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although there is no standardization in the collection methodologies for studies of fish-based IBIs in Brazil, there are some papers developing this tool in many states, especially in the South-Central region [10,35,39,[85][86][87]. However, we suggest the adoption of an electrofishing protocol as an initial step for a single regional tool that would facilitate the use of fish data collected by colleagues throughout all localities, similar to the one used by Oliveira et al [88] in Portugal.…”
Section: Discussionmentioning
confidence: 98%
“…Scientists have long recognised the importance of feeding strategies in the ecological success of animal species, but, despite the importance of invasive bass and pumpkinseed as negative drivers of native fish assemblages (Clavero et al 2013) and, in the case of bass, as a favoured angling species (Oliveira et al 2009), available information about their feeding ecology in Iberia is still limited. Investigations conducted so far have addressed a single system (García-Berthou 2002), only one species (Zapata and Granado-Lorencio 1993) or a sole sampling period (Godinho et al 1997), thus precluding a more comprehensive understanding of these species ecology in variable Iberian freshwater ecosystems.…”
Section: Introductionmentioning
confidence: 99%